The Teachable Moments on Marine Mammal Tours: Watching versus Swim-With Tours. Issue 2 (3rd March 2016) - Lück, Michael
ABSTRACT: With the continuing growth of the tourism industry over recent decades, has come a change in tourist behavior from the traditional stereotypical 3-S tourist (sun, sand, sex) to an increasingly sophisticated and demanding tourist. These "new" tourists like to learn about history, nature, and wildlife, and they expect an educational component on wildlife tours. This study investigated swim-with-dolphin tours in Kaikoura, New Zealand with regard to the educational content and the overall anatomy of these tours, using data from observations on a total of 32 tours during December 2011. The resulting data were then compared with the data from Hrycik and Forestell's study, which investigated the content of questions asked by passengers on whale-watching tours in Stellwagen Bank National Marine Sanctuary. Results of the on-tour observations indicate that the surveyed tours display a structured approach to interpretation, which is customized to the specific tour anatomy of a "swim-with" tour, and varies in some parts significantly from "watch-only" tour interpretation.